2016
DOI: 10.1080/19336918.2015.1128623
|View full text |Cite
|
Sign up to set email alerts
|

Human S100A10 plays a crucial role in the acquisition of the endometrial receptivity phenotype

Abstract: In assisted reproduction, about 30% of embryo implantation failures are related to inadequate endometrial receptivity. To identify molecules involved in endometrial receptivity acquisition, we investigated, using a SELDI-TOF approach, the protein expression profile of early-secretory and midsecretory endometrium samples. Among the proteins upregulated in mid-secretory endometrium, we investigated the function of S100A10 in endometrial receptivity and implantation process. S100A10 was expressed in epithelial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 41 publications
0
41
0
Order By: Relevance
“…Additionally, we report several known regulators of implantation, including AHNAK, S100A10, and PLAT, and human trophectoderm markers important in early implantation including cathepsin CTSC, actin ACTA2, and phosphoglucomutase 1 (PGM1) ( Table ). EpCAM (CD326) has been implicated for differentiation and survival of parietal trophoblast cells, normal development of the placental labyrinth, and establishment of a competent maternal–fetal circulation .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we report several known regulators of implantation, including AHNAK, S100A10, and PLAT, and human trophectoderm markers important in early implantation including cathepsin CTSC, actin ACTA2, and phosphoglucomutase 1 (PGM1) ( Table ). EpCAM (CD326) has been implicated for differentiation and survival of parietal trophoblast cells, normal development of the placental labyrinth, and establishment of a competent maternal–fetal circulation .…”
Section: Resultsmentioning
confidence: 99%
“…In receptive human endometrial samples, the expression of S100A10 increases during WOI. They also proved that in the nonreceptive samples, mRNA level of this protein is significantly decreased . Apoptosis plays a very important role in endometriosis during WOI, and failure of this signaling pathway (due to the reduction of S100A10 expression) can be a reason for repeated implantation failure (RIF) .…”
Section: S100 Family and Implantation Of Embryomentioning
confidence: 93%
“…Understanding of involved molecular mechanisms in achieving of endometrial receptivity phenotype will help in the success of ART. It has been reported different expression of S100A10 in a proteomic analysis of endometrial samples . Based on the results of the proteomic analysis, it seems that S100A10 protein plays effective and important role, and for this reason we focus more on this protein …”
Section: S100 Family and Implantation Of Embryomentioning
confidence: 94%
See 1 more Smart Citation
“…A study on transcriptome-based analysis in equine pregnancy revealed that S100A6 protein was expressed in conceptus side, and S100A2, S100A4, S100A6 and S100A8 were present in maternal endometrium on day 16 in mare 59 . A key role of these proteins has been suggested in epidermal growth factor-stimulated embryo adhesion, acquisition of endometrial receptivity, immunotolerance, apoptosis of dead endometrial epithelial cells and prolactin secretion, a marker for onset of decidualization 60 61 . S100 β protein is also found to be up regulated in trisomy cases, and their upregulation is an indicator of a brain lesion in developing foetus 58 .…”
Section: Role Of S100 Proteins In High-risk Pregnancy Casesmentioning
confidence: 99%